The psychopathology of crime : criminal behavior as a clinical disorder - Raine, Adrian (Academic Press, 1993)
This book takes an uncompromising look at how we define psychopathology and makes the argument that criminal behavior can and perhaps should be considered a disorder. Presenting sociological, genetic, neurochemical, brain-imaging, and psychophysiological evidence, it discusses the basis for criminal behavior and suggests, contrary to popular belief, that such behavior may be more biologically determined than previously thought. Key Features* Presents a new conceptual approach to understanding crime as a disorder * Is the most extensive review of biological predispositions to criminal behavior t.